2011
DOI: 10.1371/journal.pone.0020780
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of BMP2 Expression by the PTH-CREB Signaling Pathway in Osteoblasts

Abstract: Intermittent application of parathyroid hormone (PTH) has well established anabolic effects on bone mass in rodents and humans. Although transcriptional mechanisms responsible for these effects are not fully understood, it is recognized that transcriptional factor cAMP response element binding protein (CREB) mediates PTH signaling in osteoblasts, and that there is a communication between the PTH-CREB pathway and the BMP2 signaling pathway, which is important for osteoblast differentiation and bone formations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 55 publications
3
71
4
Order By: Relevance
“…However, ERRγ-induced Bmp2 promoter activation was still detected after deletion of 2 put-ERRE motifs or mutation of put-ERRE1, suggesting that an indirect mechanism may contribute to promoter stimulation by ERRγ. CREB is known to transacitvate BMP2 through CRE in the BMP2 promoter, 20 and we found a putative CREB-binding site on D2 −195 BMP2 promoter. Therefore, we checked whether CRE contributes to ERRγ-stimulated BMP2 promoter activation after deletion of both ERRE1 and ERRE2.…”
Section: Errγ Increases Bmp2 Promoter Activity Through Both Direct Bimentioning
confidence: 58%
“…However, ERRγ-induced Bmp2 promoter activation was still detected after deletion of 2 put-ERRE motifs or mutation of put-ERRE1, suggesting that an indirect mechanism may contribute to promoter stimulation by ERRγ. CREB is known to transacitvate BMP2 through CRE in the BMP2 promoter, 20 and we found a putative CREB-binding site on D2 −195 BMP2 promoter. Therefore, we checked whether CRE contributes to ERRγ-stimulated BMP2 promoter activation after deletion of both ERRE1 and ERRE2.…”
Section: Errγ Increases Bmp2 Promoter Activity Through Both Direct Bimentioning
confidence: 58%
“…Activation of PKA may induce CREB1 phosphorylation, and phospho-CREB1 can bind firmly to CRE, thereby inducing gene transcription (51). HA, U0126 and LY294002 have been shown to inhibit the increased binding activities of transcription factors to the FRE and HOX elements in the rat BSP gene promoter (35).…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous bone fractures observed in Pdk1 osx neonates and compound Pdk1 and Runx2 heterozygotes resemble the fractures resulting from limb-specific deletion of BMP2 (47). Additionally, recent in vitro analyses have suggested that BMP2 is a target of activated CREB in osteoblasts (48). To explore whether the PDK1 pathway is linked to the regulation of Bmp2 expression, human mesenchymal stem cells (hMSCs) or CalvObs were cultured under osteoblast differentiation conditions and treated with either PDK1 or PI3K inhibitors (Supplemental Figure 10A).…”
Section: Pdk1 Is Required For Skeletogenesis During Embryonic Developmentioning
confidence: 92%
“…Luciferase activity showed a dose-dependent increase with expression of either WT CREB or the constitutively active mutant VP16/CREB (Supplemental Figure 10C, top, and ref. 50). In addition, CREB activity was further increased in the presence of CBP, suggesting that CREB functions along with its coactivator CBP to upregulate Bmp2 expression (Supplemental Figure 10C, bottom).…”
Section: Pdk1 Is Required For Skeletogenesis During Embryonic Developmentioning
confidence: 99%